The man who fell to Earth - Watters, Dan (Titan Comics, 2022)
The film, based on the classic science fiction novel by Walter Trevis, sees an extra-terrestrial called Thomas Jerome Newton (played in the movie by David Bowie) land on Earth in search of water to save his dying home planet. Using his advanced scientific knowledge, Thomas becomes incredibly rich and uses his wealth to search for a way to transport water back to his home planet. But as his mission on Earth drags on, Thomas becomes seduced by the excesses of our world and desperate to return home unaware he has become a target of interest for the U.S. Government and a sinister corporation, eager to exploit him. The all-new graphic novel also features exclusive bonus material including a 10-page article on the production of the original film illustrated with dozens of rarely seen on-set photographs. As well as cover concepts, character designs, a 'script to art' section chronicling the development of the artwork, and a reproduction of the original movie poster."--Provided by publisher.